2006
DOI: 10.1183/09031936.06.00104905
|View full text |Cite
|
Sign up to set email alerts
|

Simplified stepwise management of primary spontaneous pneumothorax: a pilot study

Abstract: In primary spontaneous pneumothorax (PSP) requiring intervention, removal of air from the pleural space can be achieved by manual needle aspiration or by pleural drainage after insertion of a chest tube. This study aimed to evaluate the efficacy and safety of a serial-steps approach with a single system (small-calibre catheter/Heimlich valve) in a homogeneous population of patients with a first episode of PSP.All patients had an 8.5 F distally multiperforated polyurethane pigtail catheter inserted via the ante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
44
1
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 29 publications
3
44
1
5
Order By: Relevance
“…Thereafter, those who have an obvious persistent air leak on underwater seal or failure of full re-expansion could have the system replaced by the Heimlich valve. As MARQUETTE et al [9] have shown, these patients remain mobile and comfortable with this system. They could be allowed home from the emergency department to return after a further 24-48 h for further chest radiography and clinical assessment, followed either by removal of the catheter or admission for negative pressure suction or surgical intervention if air leak persists beyond 4 days.…”
mentioning
confidence: 89%
See 3 more Smart Citations
“…Thereafter, those who have an obvious persistent air leak on underwater seal or failure of full re-expansion could have the system replaced by the Heimlich valve. As MARQUETTE et al [9] have shown, these patients remain mobile and comfortable with this system. They could be allowed home from the emergency department to return after a further 24-48 h for further chest radiography and clinical assessment, followed either by removal of the catheter or admission for negative pressure suction or surgical intervention if air leak persists beyond 4 days.…”
mentioning
confidence: 89%
“…In conclusion, the pilot study presented by MARQUETTE et al [9] in this issue of the European Respiratory Journal brings us one step closer to developing a universally accepted, predominantly outpatient-based protocol for the management of primary spontaneous pneumothorax. While treatment strategies will always have to be tailored to the individual patient, emerging evidence, including that provided here, should encourage us to develop further trials to facilitate the creation of a simple sequential algorithmic approach to the general management patients with primary spontaneous pneumothorax [9,14].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In a report published previously in the European Respiratory Journal (ERJ), MARQUETTE et al [7] showed that a small-calibre catheter attached to a Heimlich valve could be safely proposed as the treatment of choice in hospitalised patients with a large PSP and potentially replace secondary (large-bore) chest tube insertion in those who fail simple manual needle aspiration. The use of a Heimlich valve may offer several advantages when compared with an underwater seal bottle system.…”
mentioning
confidence: 99%